2023
DOI: 10.1101/2023.04.30.538710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The murine meninges acquire lymphoid tissue properties and harbour autoreactive B cells during chronicTrypanosoma bruceiinfection

Abstract: The meningeal space is an important structure in the brain borders, which provides immunosurveillance for the central nervous system, but the impact of infections on the meningeal immune landscape is far from being fully understood. The extracellular protozoan parasite Trypanosoma brucei, which causes Human African Trypanosomiasis (HAT) or sleeping sickness, accumulate in the meningeal spaces, ultimately inducing severe meningitis and resulting in death if left untreated. Thus, sleeping sickness represents an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Moreover, this suggests that immunomodulatory therapies could be considered for treatment of both humans and cattle to suppress inflammation that could contribute to persistent heart disease. There is a necessity to investigate the long-term and post-treatment consequences of T. brucei -associated myocarditis to determine whether HAT patients are at increased lifetime risk of heart failure 29,46…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this suggests that immunomodulatory therapies could be considered for treatment of both humans and cattle to suppress inflammation that could contribute to persistent heart disease. There is a necessity to investigate the long-term and post-treatment consequences of T. brucei -associated myocarditis to determine whether HAT patients are at increased lifetime risk of heart failure 29,46…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is corroborated by other evidence suggesting that T. brucei -associated organ damage has an auto-immune component. A recent study found that meningeal B cells produce high-affinity autoantibodies during T. brucei infection, suggesting that autoimmune responses may be a component of T. brucei -associated pathology in multiple tissues 46 . Clinically, cardiomyopathy patients in Cameroon have been found to have high levels of both anti-trypanosomal and anti-heart antibodies, further indicating a connection between T. brucei infection and autoimmune heart disease 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation